The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1128/iai.01131-15
|View full text |Cite
|
Sign up to set email alerts
|

Maresin 1 Biosynthesis and Proresolving Anti-infective Functions with Human-Localized Aggressive Periodontitis Leukocytes

Abstract: 6 cells). Phagocytosis by LAP macrophages was reduced ϳ40% compared to that of HC, and killing of periodontal pathogens, including Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans, were similarly reduced. LAP neutrophils also displayed slower kinetics (ϳ30%) and decreased maximal phagocytosis (ϳ20% lower) with these pathogens than those of HC. The administration of MaR1 at 1 nM enhanced phagocytosis (31 to 65% increase), intracellular antimicrobial reactive oxygen species production (26 to 71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 34 publications
3
56
0
Order By: Relevance
“…Accordingly, several publications have disclosed the potential to identify and measure panels of biomarkers in saliva for diagnostic applications, discriminating patient stratification models, monitoring the progression of periodontopathogenic processes, as well as for prognosis and personalized treatment (Brinkmann, Zhang, Giannobile, & Wong, 2011;Ebersole, Nagarajan, Akers, & Miller, 2015;Ghallab, 2018;Korte & Kinney, 2016;Nagarajan, Miller, Dawson, Al-Sabbagh, & Ebersole, 2015). In this line, although some studies have suggested a role of anti-inflammatory and proresolving lipid mediators in periodontitis pathogenesis as detected in gingival crevicular fluid (GCF, Tarannum & Faizuddin, 2017), murine models (Carvalho et al, 2009;Lee et al, 2016;Van Dyke et al, 2015), cell cultures (Cianci et al, 2016;Du, Li, & Liu, 2018) and blood samples (Doğan et al, 2015;Hasturk et al, 2006;Wang et al, 2015), nothing is known regarding the salivary levels of these biomarkers and their relationship with the periodontal health/disease status. To the best knowledge of the authors, this study represents the first reference on salivary quantitation of LXA4, PD1, RvE1 and MaR1 in a representative sample of individuals with different periodontal status using a full-mouth examination along ELISA-based measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, several publications have disclosed the potential to identify and measure panels of biomarkers in saliva for diagnostic applications, discriminating patient stratification models, monitoring the progression of periodontopathogenic processes, as well as for prognosis and personalized treatment (Brinkmann, Zhang, Giannobile, & Wong, 2011;Ebersole, Nagarajan, Akers, & Miller, 2015;Ghallab, 2018;Korte & Kinney, 2016;Nagarajan, Miller, Dawson, Al-Sabbagh, & Ebersole, 2015). In this line, although some studies have suggested a role of anti-inflammatory and proresolving lipid mediators in periodontitis pathogenesis as detected in gingival crevicular fluid (GCF, Tarannum & Faizuddin, 2017), murine models (Carvalho et al, 2009;Lee et al, 2016;Van Dyke et al, 2015), cell cultures (Cianci et al, 2016;Du, Li, & Liu, 2018) and blood samples (Doğan et al, 2015;Hasturk et al, 2006;Wang et al, 2015), nothing is known regarding the salivary levels of these biomarkers and their relationship with the periodontal health/disease status. To the best knowledge of the authors, this study represents the first reference on salivary quantitation of LXA4, PD1, RvE1 and MaR1 in a representative sample of individuals with different periodontal status using a full-mouth examination along ELISA-based measurements.…”
Section: Discussionmentioning
confidence: 99%
“…n‐3s are substrates for neutrophil production of a number of classes of eicosanoids, including resolvins, protectins, and maresins, which appear key to the resolution of inflammation 24–26 . For instance, resolvins minimize excessive polymorphonuclear cell infiltration into inflamed tissues, enhancing phagocytosis and clearance of apoptotic cells and microbes 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The MaR1 pathway is temporally regulated during self-limited sterile inflammation, with levels of its pathway marker 14-HDHA reaching a maximum during the resolution phase (4). MaR1 also enhances macrophage phagocytosis of Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans (22). MaR1 may also be produced by eosinophils given that these cells express the murine homologue of initiating enzyme in the MaR1 metabolome; in addition these leukocytes are also known to produce SPM including PD1, RvD5 and LXA 4 during sterile peritonitis (23).…”
Section: Discussionmentioning
confidence: 99%
“…MaR1 also potently regulates host responses to bacteria, stimulating phagocytosis and killing of oral pathogens by human leukocytes (22). In the present report we investigated the temporal regulation of MaR1 during self-limited infections.…”
Section: Discussionmentioning
confidence: 99%